Spatial Heterogeneity of Soil Respiration Response to Precipitation Pulse in a Temperate Mixed Forest in Central China - Liu, Yanchun; Shang, Qing; Wang, Zhongwei; Zhang, Kesheng; Zhao, Cancan (Journal of Plant and Animal Ecology, 2017)
Water availability is one of the fundamental drivers for biological activities and terrestrial carbon cycling. Although the response of soil respiration to precipitation has been well documented in arid and semiarid ecosystems, our understanding of its pattern in forests is rather limited. This study was conducted to examine the difference of precipitation effect on soil respiration under different canopy conditions in a temperate coniferous (Pinus armandii Franch) and broadleaved (Quercus aliena var. acuteserrata) mixed forest in Central China. The results showed that precipitation significantly reduced soil temperature, but increased soil volumetric water content and soil respiration (6.0%-35.3%). Precipitation caused a greater increment in soil respiration beneath the canopy of broadleaved trees (24.2%) than that beneath coniferous ones (13.5%). Precipitation-induced increase in soil respiration was consistently lower beneath the canopy of small size classes (7.1%-32.6%) than large size classes (9.5%-33.3%). Mean soil respiration of forest gaps increased 22.4% following precipitations. Our study highlights the positive response of soil respiration to precipitation pulses in water-unlimited ecosystems. The findings suggest that the spatial heterogeneity of soil respiration to precipitation pulse under different canopy conditions should be emphasized while assessing terrestrial carbon cycling and its feedback to climate change.
Keywords: CO2 efflux; spatial variation; rainfall; birch effect; canopy size